A practical guide to fiberglass pole vaulting - Bussabarger, D. (Track Coach, 2020)
This article, by longtime vault observer Bussabarger, is a brief synopsis of fiberglass vaulting technique. Bussabarger has studied a large number of accomplished vaulters over the years and has made conclusions based on analysis of their technique. Perhaps the most important takeaway of this study is that there has always been a great deal of individual variation in execution among the best vaulters and there is no hard-and-fast one way to vault